2010
DOI: 10.1002/cncr.24892
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G is present in a wide variety of soft tissue tumors and correlates well with proliferation markers and tumor grades

Abstract: BACKGROUND:The traditional view that immunoglobulin (Ig) is produced only by B lymphocytes has been challenged, because it has been demonstrated that Ig genes and proteins are expressed in epithelial cancer cells. However, whether Ig expression in nonlymphoid cells is limited to epithelial cells is unclear. Because sarcomas differ distinctly from carcinomas in their biologic and clinical features, the authors investigated the question of nonlymphoid IgG expression in soft tissue lesions. METHODS: Immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 35 publications
(34 reference statements)
4
50
1
Order By: Relevance
“…Besides cancer cells of epithelial cell origins, the majority of soft tissue tumors (Chen et al, 2010;Liu et al, 2012;Qiu et al, 2012b), such as sarcomas, were also found to express immunoglobulins, with the level of these atypical immunoglobulins correlating with markers of proliferation (PCNA, KI67, cyclin D1) and tumor grades (Zhang et al, 2012). Based on the results of this study, it was concluded that the expression of atypical immunoglobulins was a common characteristic of all human cancers (Chen et al, 2009;Hu et al, 2008;Kimoto, 1998;Lee and Ge, 2009).…”
Section: Expression Of Immunoglobulins By Normal and Cancer Cells Inmentioning
confidence: 59%
“…Besides cancer cells of epithelial cell origins, the majority of soft tissue tumors (Chen et al, 2010;Liu et al, 2012;Qiu et al, 2012b), such as sarcomas, were also found to express immunoglobulins, with the level of these atypical immunoglobulins correlating with markers of proliferation (PCNA, KI67, cyclin D1) and tumor grades (Zhang et al, 2012). Based on the results of this study, it was concluded that the expression of atypical immunoglobulins was a common characteristic of all human cancers (Chen et al, 2009;Hu et al, 2008;Kimoto, 1998;Lee and Ge, 2009).…”
Section: Expression Of Immunoglobulins By Normal and Cancer Cells Inmentioning
confidence: 59%
“…Most of the non-B cell-expressed immunoglobulins were found in tissues containing hyperplastic epithelial cells, including those of the skin, esophagus, cervix, and immune privileged sites, such as in the eyes, testis, brain neuron, and placenta [31]. Due to the lack of experimental evidence, the immunoglobulin expressions among these normal tissues could only be explained by the assumption that they may be required for immune protection [17,27,[33][34][35][36][37][38][39].…”
Section: Expressions Of Immunoglobulins and Ca215 From Non-b Cellsmentioning
confidence: 99%
“…[2][3][4][5] IgG expression has also been found in colon carcinoma, breast carcinoma, lung carcinoma, and soft tissue tumors. [6][7][8][9] The exact function of IgG in cancers has not yet been elucidated, but IgG might be involved in the promotion of tumor growth based on preliminary in vitro evidence of its capacity to stimulate cell proliferation and invasion. 6,10 Another observation supporting a growth-promoting role of IgG include the observed correlation between the level of IgG expression and tumor grade and stage in soft tissue tumors.…”
mentioning
confidence: 99%
“…6,10 Another observation supporting a growth-promoting role of IgG include the observed correlation between the level of IgG expression and tumor grade and stage in soft tissue tumors. 9 To date, it is not known whether papillary thyroid cancer cells also produce IgG. Lucas et al, 11 detected cellular deposits of IgG in 80% of 41 papillary thyroid cancer cases studied.…”
mentioning
confidence: 99%